Machine Learning and Human Factors: Status, Applications, and Future Directions. (September 2018) - Lau, Nathan; Fridman, Lex; Borghetti, Brett J.; Lee, John D.
As machine learning approaches ubiquity in industrial systems and consumer products, human factors research must attend to machine learning, specifically on how intelligent systems built on machine learning are different from early generations of automated systems, and what these differences mean for human-system interaction, design, evaluation and training. This panel invites five researchers in different domains to discuss how human factors can contribute to machine learning research and applications, as well as how machine learning presents both challenges and contributions for human factors.